ANALISIS PERMINTAAN KEDELAI DI KABUPATEN BANYUMAS JAWA TENGAH - DEWI SAHARA; ENDANG S. GUNAWATI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Soybean demand analysis research in Banyumas regency used time series data from1994 – 2003. Soybean demand function was estimated by double dynamic linear regressionanalysis model in logarithm with put last year demand variable. Analysis result showed thefactor affected soybean demand were price of soybean, population, and price of corn.Decreasing of soybean demand was caused by decreasing of soybean price and corn price.The demand will increase together with increase in population. Soybean demand was elasticto both price change and income change. This meant that increasing of income may causeincreasing of soybean quantity on each increasing of price, so soybean was normal goods.Elasticity crossed obtained was smaller than one (EQ,P1 < 1), so it was complementrelationship between corn and soybean. Short run soybean demand elasticity value waslarger than long run demand. It meant that in short run, demand change was directlyinfluenced by change of price and income, but in long run context, its change response tendsto decrease due to adaptation process.